Concept of Domination According to Theravad Buddhist Philosophy - Sukbumrungsub, Hemaluk; Thongpun, Suwin; Komaro, PhraChaiya; Athipanyo, PhraatikarnPramaul; Boriboon, Pairote (Journal of Graduate MCU KhonKaen Campus, 2023)
The objective of this research was 1) To study the concept of governance 2) To study governance of the philosophy Theravad Buddhism. and 3) To study and analyze the concept of governance based on the philosophy of Theravad Buddhism is documentary research. The first document to study the Buddhist scriptures, second document, Academic papers and related research. Descriptive data are analyzed according to induction. Research has found that The government is the legitimate sovereignty of national administration and management, and is the mode of interpersonal relationship. Reach mutual agreement between parents and subordinates to provide people with good living conditions and social peace, including physical peace. At present, there are two forms of rule dictatorship and democracy. The rule of Buddhist philosophy is to manage human beings in an orderly and fair way through fair and equal ways. There are two forms to solve social problems equally monarchy and unity. The ruling philosophy of Buddhism is to support the rule with Buddhism and compassion. By using the Sangha system, the principle of Sangha rule is used in the regime to achieve peace, which is called Buddhism.